Investigação sobre o sistema circulatório no ensino fundamental: planejamentos e atividades - Christo, Thanara Muraro de (2019)
This dissertation investigates the teaching of the circulatory system in Elementary School, being this subject of complexity and abstraction typical of the teaching of Sciences. The research was developed in two approaches: analysis of lesson plans and analysis of a teaching proposal through the use of narrative. The research took place in three phases: in the first stage, the study and analysis of lesson plans, intended for the teaching of the circulatory system for Elementary School students. The analyzed plans were suggestions of classes available in the virtual platform of the Ministry of Education called Teacher Portal. The objective was to investigate the presence of trends or patterns of structure of lesson plans and the use of didactic resources. In the second stage, after analyzing the circulatory system content in primary school textbooks, a text was produced with elements of narrative language to explain the process of blood circulation. Participated in this research students from three classes of sixth grade of elementary school in a federal public school in the year 2018. Prior to the application of this material, students' prior knowledge was investigated through a questionnaire. The reading of the text was accompanied by activities of image identification and resolution of questions with answers of understanding and interpretation of the text. Forty-five days after the activities an evaluation questionnaire was applied on the content of the text and a writing activity evaluating from the point of view of the students the material used. The results of the first phase of the research indicated that the suggestions of classes available in the Teacher Portal do not present a common pattern of structure, although they are on the same platform The evaluation process is poorly defined and rather superficial. The third step contains analysis of the data obtained in the second stage. The application of the text with elements of narrative suggest that the development of the activities may have contributed to the students' understanding of the subject, since they were able to express the main idea of the content present in the material. Both the analysis of the textbooks and the lesson plans concluded that there is little presence of elements of narrative in the material for elementary school and the inclusion of narratives can be a facilitating strategy for the teaching process learning of a complex theme such as circulatory system .